Montažna eko-gradnja - Zupančič-Strojan, Tadeja (Les (Ljubljana), 1999)
Survey of the latest findings about possibilities and limitations of using timber as construction elements in the era of changing consumer into eco-culture indicates a gap between specific circumstances of cultural environment and existing offer. This gap, which enlarges with the richness of complexity of settlement landscape, was obvious also from the results of the last symposium on pre-fabricated houses in Slovenia. The discussion below should challenge some ideas to be discussed during the next convention. Development orientation should lead from multi- to interdisciplinarity of development co-ordination, from specific technologies for general markets to universal production for specialised and local needs and from adjusting to circumstances to deriving from them.
Keywords: architecture; arhitektura; urbanistično načrtovanje; les; montažna gradnja; identiteta